Formulation and Evaluation of Herbal Antiperspirant and Deodorant Foot Powder from Mulberry Leaves Extract - Ravindran Muthukumarasamy (Journal of Global Pharma Technology, 2018)
Background: Sweating is a normal physiological process occurs in the body, but excessive sweating (hyperhidrosis) indicates a significant adverse impact on the quality of life for individuals. Sweating can be considered to have stressful experience, reduces self-confidence and social acceptance as it interferes with daily activities. Excessive sweating on the foot provides optimum conditions for bacterial growth and subsequently leads to smelly foot. Objective: The objective of the current study was to formulate and evaluate antiperspirant and deodorant foot powder from mulberry leaves extract.  Methods: The formulated powder was tested for its antiperspirant and deodorant activity against Staphylococcus epidermidis by measuring its zone of inhibition using disk diffusion method. Furthermore, the formulated powder was tested for its physiochemical parameters as per standard procedures. Results: The study results proved that mulberry leaf extract showed considerable antibacterial activity against Staphylococcus epidermidis bacteria in concentration of 200 mg/ml and 400 mg/ml. Phytochemical screening on the extract confirmed the presence of alkaloids, reducing sugars, phenols, flavanoids, carbohydrates, proteins, etc... The invitro evaluation of  the formulated herbal foot powder was tested on the micrometric test parameters like angle of repose, bulk density, tapped density, hausner ratio, carrs compressibility index and sterility test. The results on the micrometric properties was found to have poor flow property. Conclusion:However, the formulated herbal foot powder from mulberry leaves extract can be used as a potential herbal antiperspirant and deodorant foot powder with further studies on improving the flow property of the powder and toxicity testing using suitable models.